Public finance reform in Malaysia : issues and challenges - Mohd Asrul Hery Ibrahim; Mohd Rushdan Yasoa; Mohd Safwan Ghazali; Cherine Lim (Faculty of Entrepreneurship and Business,UMK, 2015)
The objective of this paper is to address briefly governments’ efforts on economic transformation and some of the changes of systems through public finance reform policy. The public finance reform initiatives are believed will strengthen country’s financial position and reduce government’s debt to cushion the economy against external shock. Some of the vital initiatives under public finance reform are accrual accounting system and good and service tax (GST). Therefore, this paper will discuss and dispute the implementation of the accrual accounting system in the public sector and elaborate the issues and challenges pertaining to the changes of taxation system.